Cancer, immunodeficiency and antiretroviral treatment: results from the Australian HIV Observational Database (AHOD). Issue 2 (30th August 2012) - Petoumenos, K; van Leuwen, MT; Vajdic, CM; Woolley, I; Chuah, J; Templeton, DJ; Grulich, AE; Law, MG; ,
Abstract : Objectives: The objective of the study was to conduct a within‐cohort assessment of risk factors for incident AIDS‐defining cancers (ADCs) and non‐ADCs (NADCs) within the Australian HIV Observational Database (AHOD). Methods: A total of 2181 AHOD registrants were linked to the National AIDS Registry/National HIV Database (NAR/NHD) and the Australian Cancer Registry to identify those with a notified cancer diagnosis. Included in the current analyses were cancers diagnosed after HIV infection. Risk factors for cancers were also assessed using logistic regression methods. Results: One hundred and thirty‐nine cancer cases were diagnosed after HIV infection among 129 patients. More than half the diagnoses ( n = 68; 60%) were ADCs, of which 69% were Kaposi's sarcoma and 31% non‐Hodgkin's lymphoma. Among the NADCs, the most common cancers were melanoma ( n = 10), lung cancer ( n = 6), Hodgkin's lymphoma ( n = 5) and anal cancer ( n = 5). Over a total of 21021 person‐years (PY) of follow‐up since HIV diagnosis, the overall crude cancer incidence rate for any cancer was 5.09/1000 PY. The overall rate of cancers decreased from 15.9/1000 PY [95% confidence interval (CI) 9.25–25.40/1000 PY] for CD4 counts < 100 cells/μL to 2.4/1000 PY (95% CI 1.62–3.39/1000 PY) for CD4 counts > 350 cells/μL. Lower CD4 cell count and prior AIDS diagnoses were significant predictors for both ADCs and NADCs. Conclusions: ADCs remain the predominant cancers in this population, although NADC rates have increased in the more recent time period. Immune deficiency is a risk factor for both ADCs and NADCs.